TINDAK PIDANA PEMBOBOLAN KARTU KREDIT MELALUI INTERNET DI INDONESIA DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG ITE - B. Myko Hasibuan (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2020)
Factors That Cause Crime Credit Card Breaking Through the Internet Linking Information Law and Electronic Transactions are Internal factors are factors that are found in individuals (credit card criminals), which consist of Education Factors etc. Law Enforcement Against Crime of Credit Cards Through the Internet Linked to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 Concerning ITE are provisions that can be imposed on people suspected of having broken into customers through regulated credit cards Article 4 letter (e) of the ITE Law is to provide a sense of security, justice and legal certainty for users and providers of information technology. Key Words : Crime, Credit Card Breaking, Internet